การศึกษาความสัมพันธ์ระหว่างปัจจัยส่วนประสมทางการตลาดและการบริโภคสินค้าอินทรีย์ - สุขรัตน์, คณิต; อธินุวัฒน์, ดุสิต (Thai Journal of Science and Technology, 2019)
Abstract This study investigated the relationship between marketing mix factors and organic product consumption by sampling the populations of 400 organic product consumers in Bangkok area. Results revealed that the marketing mix factors including product, price, place and promotion affecting organic product consumption of organic product consumer, showed the correlation with organic product consumption. Product factor variables and price factor variables showed highest correlation coefficient with r = 0.462 (p = 0.01). Price factor variables and promotion factor variables showed lowest correlation coefficient with r = 0.165 (p = 0.01). The pair of product factor variables and promotion factor variables (r = 0.024) and the pair of place factor variables and promotion factor variables (r = 0.081) did not showed the correlation with organic product consumption. Overall results revealed that the 3 highest factors correlated with organic product consumption were organic product make people healthy (P1), organic distributed place is convenience for transportation (P9), and organic product price is suitable to its quality (P5) with the r values of 0.517, 0.383, and 0.354, respectively. The 3 lowest factors correlated with organic product consumption were government and private sectors supporting organic products (P14), organic product promotion (P13), and trust of organic certification system (P3) with the r values of 0.104, 0.126, and 0.320, respectively. This information is beneficial to promote organic product consumption and organic product market extension. Keywords: marketing mix factor; organic product; consumption behavior; organic farming